The Great Peace of Montreal of 1701 French-native diplomacy in the seventeenth century - Havard, Gilles 1967- (McGill-Queen's Univ. Press, 2001)
"In The Great Peace of Montreal of 1701 Gilles Havard brings to life the European and Native players who brought about this major feat of internatioanl diplomacy. He highlights the differing interests and strategies of the numerous nations involved while giving a dramatic account of the colourful conference. The treaty, Havard argues, was the culmination of the French colonial strategy of Native alliances and adaptation to Native political customs. It illustrates the extent of cultural interchange between the French and their Native allies and the crucial role the latter played in French conflicts with the Iroquois and the British." "As we approach the three hundredth anniversary of the treaty's signing in August 1701, Gilles Havard emphasizes its contemporary significance: in signing a treaty with forty separate parties the French recognized the independent sovereignty of every Native nation. This translation is significantly revised and updated from the original French publication of 1992."--BOOK JACKET.